The Use and Preference of Functional Appliances among a Sample of Iraqi Orthodontists: A Web-Based Survey - Hiba M. Hussien; Zena Hekmat Altaee; Mohammed Nahidh; Sajid Chaffat Auliawi Al-Mayahi (Hindawi Limited, 2022)
Objectives. This study evaluated the use and preference of different types of functional appliances among a sample of Iraqi orthodontists. Materials and Methods. About 200 orthodontists were invited to fill out an online Google form questionnaire with multiple-choice questions. The questions were modified from previous England and Malaysian studies. The data were tabulated as frequency tables. Results. The response rate was 61%. About 91.80% of the participants used functional appliances, with the removable type being the most used. The twin block was thought to be the best compliance one but not the most used functional appliance. About 62% depended on the clinical observations in determining the growth spurt and asked patients to wear the appliance full-time except at meal time. The majority preferred a period of retention of about 4-6 months and frequent visits for adjustments. Conclusions. Removable functional appliances are the most frequently used among the studied sample.